Protecting the vulnerable: addressing the COVID-19 care needs of people with compromised immunity - Razonable, Raymund R. (Frontiers in Immunology, 2024)
While the general population regained a certain level of normalcy with the end of the global health emergency, the risk of contracting COVID-19 with a severe outcome is still a major concern for people with compromised immunity. This paper reviews the impact of COVID-19 on people with immunocompromised status, identifies the gaps in the current management landscape, and proposes actions to address this unmet need. Observational studies have demonstrated that people with immune dysfunction have a higher risk of COVID-19-related hospitalization and death, despite vaccination, than the general population. More research is needed to define the optimal prevention and treatment strategies that are specific to people with immunocompromised status, including novel vaccination strategies, monoclonal antibodies that provide passive immunity and complement suboptimal vaccination responses, and improved and safer antiviral treatment for COVID-19. Preventive measures beyond vaccination alone are urgently needed to protect this vulnerable population.